The integrated stress response prevents demyelination by protecting oligodendrocytes against immune-mediated damage - Lin, Wensheng (American Society for Clinical Investigation, 2007)
In response to ER stress, the pancreatic endoplasmic reticulum kinase (PERK) coordinates an adaptive program known as the integrated stress response (ISR) by phosphorylating the α subunit of eukaryotic translation initiation factor 2 (eIF2α). IFN-γ, which activates the ER stress response in oligodendrocytes, is believed to play a critical role in the immune-mediated CNS disorder multiple sclerosis (MS) and its mouse model, experimental autoimmune encephalomyelitis (EAE). Here we report that CNS delivery of IFN-γ before EAE onset ameliorated the disease course and prevented demyelination, axonal damage, and oligodendrocyte loss. The beneficial effects of IFN-γ were accompanied by PERK activation in oligodendrocytes and were abrogated in PERK-deficient animals. Our results indicate that IFN-γ activation of PERK in mature oligodendrocytes attenuates EAE severity and suggest that therapeutic approaches to activate the ISR could prove beneficial in MS.